Social Cartography. A map of journalistic research programs in Argentina - Justo von Lurzer, Carolina (2022)
The present work aims at developing the particular link that journalistic research programs establish with the reality represented with two modalities as starting points: commitment (complaint) and (surveillance) protection. These links are established from the characterization of a social cartography whose limits are framed in the relationship with certain subjects, spaces, and practices: those located on the margins and the conflict with law or social norms. A reflection on the functions which these operations build for television as a means: surveillance of context and modeling subjects and practices is also provided.